The potentials of embodied and ethnomathematical perspectives for Caribbean mathematics education - Khan, Steven (School of Education, UWI, St. Augustine, 2008)
This paper explores the potential value of adopting embodied and ethnomathematical perspectives in the specific context of mathematical education in Trinidad and Tobago. It is suggested that ideas representing overlaps among the domains of embodied cognition and ethnomathematics are manifested in the reform-oriented mathematics curriculum documents of the Trinidad and Tobago Secondary Education Modernization Programme (SEMP), and a simple example is provided of one area where such an investigation might potentially begin
Keywords: Mathematics education; Embodied mathematics; Ethnomathematics; Curriculum development; Secondary school curriculum; Trinidad and Tobago